Pulse-Controlled Amplification–A new powerful tool for on-site diagnostics under resource limited conditions - Müller, Katharina; Daßen, Sarah; Holowachuk, Scott; Zwirglmaier, Katrin; Stehr, Joachim; Buersgens, Federico; Ullerich, Lars; Stoecker, Kilian (PLOS Neglected Tropical Diseases, 2021)
Background Molecular diagnostics has become essential in the identification of many infectious and neglected diseases, and the detection of nucleic acids often serves as the gold standard technique for most infectious agents. However, established techniques like polymerase chain reaction (PCR) are time-consuming laboratory-bound techniques while rapid tests such as Lateral Flow Immunochromatographic tests often lack the required sensitivity and/or specificity. Methods/Principle findings Here we present an affordable, highly mobile alternative method for the rapid identification of infectious agents using pulse-controlled amplification (PCA). PCA is a next generation nucleic acid amplification technology that uses rapid energy pulses to heat microcyclers (micro-scale metal heating elements embedded directly in the amplification reaction) for a few microseconds, thus only heating a small fraction of the reaction volume. The heated microcyclers cool off nearly instantaneously, resulting in ultra-fast heating and cooling cycles during which classic amplification of a target sequence takes place. This reduces the overall amplification time by a factor of up to 10, enabling a sample-to-result workflow in just 15 minutes, while running on a small and portable prototype device. In this proof of principle study, we designed a PCA-assay for the detection of Yersinia pestis to demonstrate the efficacy of this technology. The observed detection limits were 434 copies per reaction (purified DNA) and 35 cells per reaction (crude sample) respectively of Yersinia pestis. Conclusions/Significance PCA offers fast and decentralized molecular diagnostics and is applicable whenever rapid, on-site detection of infectious agents is needed, even under resource limited conditions. It combines the sensitivity and specificity of PCR with the rapidness and simplicity of hitherto existing rapid tests.